2019
DOI: 10.29289/25945394201920190006
|View full text |Cite
|
Sign up to set email alerts
|

The implementation of patient navigation to improve mammography coverage and access to breast cancer care in Rio de Janeiro

Abstract: Este estudo avalia a introdução do Programa de Navegação do Paciente (PNP) em uma comunidade do município do Rio de Janeiro. Os objetivos são: estabelecer a viabilidade do PNP nesse contexto; identificar as barreiras ao rastreamento mamográfico; e assegurar cobertura mamográfica de 70% das mulheres recrutadas entre 50 e 69 anos. De março a setembro de 2018, foram recrutadas 678 mulheres com idade média de 58 anos da comunidade do Andaraí. O acompanhamento foi realizado pelo navegador de pacientes (NP) por tele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The initial goal was compliance with the law in at least 70% 6 , but chronic structural problems in Rio de Janeiro, such as a deficit of human resources and medical supplies, made it difficult to achieve this goal. Local managers were informed of the structural improvement needs involving partnerships from municipal, state, and federal powers [23][24][25] .…”
Section: Discussionmentioning
confidence: 99%
“…The initial goal was compliance with the law in at least 70% 6 , but chronic structural problems in Rio de Janeiro, such as a deficit of human resources and medical supplies, made it difficult to achieve this goal. Local managers were informed of the structural improvement needs involving partnerships from municipal, state, and federal powers [23][24][25] .…”
Section: Discussionmentioning
confidence: 99%
“…Seventy-five percent of the patients had advanced disease at diagnosis, 40% of the patients were considered young, that is, under 50 years of age, and 28% of the patients had a family history of BC, indicating the importance of expanding patient navigation for primary health care 19 . All patients with family risk reported that they were never instructed about the risks of the disease and how to protect their family members (change in lifestyle, screening for high-risk population, genetic counseling, genetic testing, and prophylactic interventions).…”
Section: Discussionmentioning
confidence: 99%
“…Effective actions in the management of care and acting on the main barriers to early detection of BC can favor adherence to personalized mammographic screening, timely investigation, and access to treatment. The PN experience in the Andaraí community, in the municipality of Rio de Janeiro, showed an increase in the tracking rate from 14% to 84%, and 100% of the lesions in 2018 were diagnosed in initial staging 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Gioia S, Brigagão L, Torres C, Lima A, Medeiros M. 2019 (28) Establish the viability of patients' navigation program in a community in the city of Rio de Janeiro; identify barriers to mammographic screening; mammographic coverage of 70% of women recruited between 50 and 69 years old. MMG request by physicians.…”
Section: Flexibility Of Goals Considering Viabilitymentioning
confidence: 99%
“…By developing the skills expected in PHC beyond the gateway, the strategy of patient navigation by a Community Health Worker (CHW), in addition to showing the best result (28) , allowed us to move towards a vision that considered users and their subjectivities in the social process of building the disease. The patient navigation program consists of a trained team that helps patients to overcome modifiable barriers to care based on a personalized approach (35) .…”
Section: Flexibility Of Goals Considering Viabilitymentioning
confidence: 99%